2021
DOI: 10.1155/2021/5531830
|View full text |Cite
|
Sign up to set email alerts
|

Selection of an Effective Hand Sanitizer to Reduce COVID‐19 Effects and Extension of TOPSIS Technique Based on Correlation Coefficient under Neutrosophic Hypersoft Set

Abstract: Correlation coefficients are used to tackle many issues that include indistinct as well as blurred information excluding is not able to deal with the general fuzziness along with obscurity of the problems that have various information. The correlation coefficient (CC) between two variables plays an important role in statistics. Likewise, the accuracy of relevance assessment depends on the information in a set of discourses. The data collected for numerous statistical studies is full of exceptions. The concept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…The selection of an effective hand sanitizer to reduce the effects of COVID-19 is a critical decision in the current global health crisis. An extension of the TOPSIS technique based on correlation coefficients under the NHSS presents by Samad [38] an innovative approach to this problem. Kalaichelvi [39] conducted a study that applied fuzzy soft sets to investment decision-making problems.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of an effective hand sanitizer to reduce the effects of COVID-19 is a critical decision in the current global health crisis. An extension of the TOPSIS technique based on correlation coefficients under the NHSS presents by Samad [38] an innovative approach to this problem. Kalaichelvi [39] conducted a study that applied fuzzy soft sets to investment decision-making problems.…”
Section: Introductionmentioning
confidence: 99%
“…The study of fractional-order COVID-19 infection model gradually attracted the researchers interests and attention. [42][43][44][45][46] The utilization of the fractional-order derivatives to COVID-19 infection model can describe their dynamics more precisely. The Caputo fractional derivatives and integrals are the most well known operators, historically been used for modeling many real world problems.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the data collected from real‐life phenomena fits better with fractional order system. The study of fractional‐order COVID‐19 infection model gradually attracted the researchers interests and attention 42–46 . The utilization of the fractional‐order derivatives to COVID‐19 infection model can describe their dynamics more precisely.…”
Section: Introductionmentioning
confidence: 99%
“…e basics of the hypersoft set, such as complement, non-set, hypersoft subset, and aggregation operators, were then presented by Saeed et al [25]. Several scholars have looked into different operators and features under the hypersoft set and its expansions [26][27][28][29][30]. e theme of the fuzzy intuitionistic soft set was then extended and a new theme of the intuitionistic fuzzy hypersoft set was established, as well as aggregation operators for solving MADM problems by Zulqarnain [31].…”
Section: Introductionmentioning
confidence: 99%